Emerging Trends in Biomaterials for Cancer Immunotherapy and Genome Editing: A Comprehensive Review - Bhat, Ramdas; Shanbhag, Preeti (Indian Journal of Pharmacy & Drug Studies, 2024)
This detailed review navigates the dynamic landscape of cancer therapeutics, shifting focus from conventional approaches to the promising frontiers of immunotherapy and genome editing. Biomaterials, including nanoparticles and hydrogels, are scrutinized for their role in enhancing therapeutic efficacy across various cancer types. Breakthroughs in biomaterial based interventions are emphasized, with a meticulous examination of critical methodological considerations, such as safety, biocompatibility, and de li very efficiency, laying the groundwork for future research. The narrative emphasizes the need for standardization and regulatory compliance to ensure the safety and reliability of emerging therapies moving towards clinical applications. Implications for the ory, practice, and future research highlight the potential of biomaterial based approaches to offer safer and more effective cancer treatments. The integration of personalized medicine is advocated, emphasizing tailored interventions based on individual pa tient profiles. The review underscores the multidisciplinary collaboration across materials science, immunology, and oncology as essential for a holistic understanding and effective development of biomaterial based therapies. Overall, this review contribute s to the ongoing shift towards safer, more efficacious, and personalized cancer therapeutics by exploring innovative avenues in immunotherapy and genome editing, while emphasizing the need for a methodologically rigorous approach in translating these advan cements to clinical practice.